Google Classroom Training for Chemical Education Study Program - Lukman Hadi; Masriani Masriani; Husna Amalya Melati; Rody Putra Sartika (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2020)
The purpose of implementing this PKM is to improve the understanding and skills of Chemistry Education lecturers and students in the use of e-learning through the Google Classroom application in chemistry learning. In addition, it is also to increase the number of lecturers who use Google Classroom. The training was conducted at the FKIP Tanjungpura University Hall. Participants consisted of lecturers and students from the 2019/2020 class. The  activity was divided into five sessions. The first session was preparation. The second session was the delivery of material about google classroom by Rody Putra Sartika, M.Pd, and Husna Amalya Melati, M.Sc. The third session was a demonstration of using the Google Classroom application as a learning media. The fourth session was mentoring. During this activity, the participants were allowed to ask questions about things they did not understand. The last session was an evaluation of the activity implementation. The training results concluded that the training went well and received a positive response from the participants. The knowledge and skills of participants have increased. The number of lecturers using Google Classroom increased from 20% to 47%. With the use of Google Classroom in chemistry learning, it is hoped that it will improve the quality of graduates from Chemistry Education Study Program